(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A well-known and highly valued cultural plant, lemongrass (Cymbopogon citratus) has a long history of usage in aromatherapy, cooking, and traditional medicine. This in-depth review study attempts to give a full overview of lemongrass, taking into account its botanical features, phytochemical makeup, pharmacological activities, and medicinal uses. The taxonomic division, geographic range, and physical characteristics of lemongrass are clarified in the botanical portion of this paper. The essential kinds of lemongrass are distinguished, and their adaptation to diverse environmental situations is emphasised. The broad variety of bioactive components found in lemongrass, such as citral, citronellal, myrcene, and limonene, are highlighted by the phytochemical makeup of the herb, which is discussed in the section that follows. These ingredients give lemongrass its characteristic scent and are the basis for all of its beneficial pharmacological activities. The pharmacological component of this paper explores lemongrass’s possible medicinal uses, including its antibacterial, anti-inflammatory, antioxidant, anti-cancer, and antidiabetic characteristics. The study also explores the mechanisms behind these actions, elucidating the interactions of lemongrass constituents with biomolecules and cellular processes. In-depth research is done on the medicinal uses of lemongrass, including its integration into both conventional and alternative medical systems across the world. It has been demonstrated that lemongrass is effective in treating a variety of health issues, including skin problems, anxiety, and digestive problems. This study also examines lemongrass’s safety profile and any potential risks associated with its ingestion, emphasising the need for responsible use and care in particular groups.